2015
DOI: 10.3748/wjg.v21.i31.9239
|View full text |Cite
|
Sign up to set email alerts
|

OralCampylobacterspecies: Initiators of a subgroup of inflammatory bowel disease?

Abstract: In recent years, a number of studies detected a significantly higher prevalence of Campylobacter species such as Campylobacter concisus (C. concisus) in intestinal biopsies and fecal samples collected from patients with inflammatory bowel disease (IBD) compared to controls. Most of these Campylobacter species are not of zoonotic origin but are human oral Campylobacter species. Bacterial species usually cause diseases in the location where they colonize. However, C. concisus and other oral Campylobacter species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 32 publications
(40 reference statements)
2
50
0
1
Order By: Relevance
“…The core-genome, the sequences of six housekeeping genes and the 23S rRNA gene consistently assigned these C. concisus strains into two genomospecies (Figs 1, 2, 3). The enteric strains did not form distinct groups within both genomospecies, further supporting our previous theory that some oral C. concisus strains may cause enteric disease when colonizing the intestinal tract33132. The previous study examining eight C. concisus strains reported that 16S rRNA gene of C. concisus strains was able to differentiate C. concisus strains isolated from patients with CD and gastroenteritis, this was not observed in our study where 36 C. concisus strains were examined (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The core-genome, the sequences of six housekeeping genes and the 23S rRNA gene consistently assigned these C. concisus strains into two genomospecies (Figs 1, 2, 3). The enteric strains did not form distinct groups within both genomospecies, further supporting our previous theory that some oral C. concisus strains may cause enteric disease when colonizing the intestinal tract33132. The previous study examining eight C. concisus strains reported that 16S rRNA gene of C. concisus strains was able to differentiate C. concisus strains isolated from patients with CD and gastroenteritis, this was not observed in our study where 36 C. concisus strains were examined (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Bacteria generally cause a disease where they colonize, but C. concisus is unusual in that the colonization site of C. concisus is normally the oral cavity, but the species is associated with gastrointestinal diseases like IBD. C. concisus is capable of colonizing the intestine, possibly by producing unique virulence factors only expressed in the intestinal environment (Zhang, 2015). Although related pathogenesis mechanism is unclear yet, these results indicate that C. concisus may be related to initiation of IBD.…”
Section: Ibdmentioning
confidence: 75%
“…Although the cause of IBD is poorly understood, it is assumed that IBD occurs in humans because of a genetic predisposition and is triggered by an environmental factor (Sartor, 2006). In a review by Zhang (2015), a number of studies are cited that reported that Campylobacter spp. was detected at significantly higher prevalence in intestinal samples from IBD patients.…”
Section: Ibdmentioning
confidence: 99%
See 2 more Smart Citations